Interactions of Single Mepiquat Chloride Application at Different Growth Stages with Climate, Cultivar, and Plant Population for Cotton Yield. Issue 3 (16th June 2017) - Zhao, Wenchao; Du, Mingwei; Xu, Dongyong; Lu, Huaiyu; Tian, Xiaoli; Li, Zhaohu
Abstract : Cotton ( Gossypium hirsutum L.) yield responses to the plant growth regulator mepiquat chloride (1, 1‐dimethyl piperidinium chloride, MC) are associated with climate, cultivar, and plant population. However, the interactions of these factors with MC for yield are inconsistent or unexpected. We hypothesize that climate (mainly precipitation), cultivar, and plant density only interact with MC applied at specific growth stages to affect yield. Experiments were thus conducted in two contrasting years (2013–2014). Mepiquat chloride was applied at the seedling, squaring, early bloom, full bloom, and post‐topping of the main stem (close to the time of cutout) stages. Plant populations were 6.5 and 11.4 plants m −2, and the two cultivars SCRC36 and Han7860 were used. The results showed that the yield averaged over all treatments significantly increased by 5.6, 5.0, and 6.1% because of MC application at the seedling, early bloom, and full bloom stages, respectively. Additionally, the interaction of the year (climate) × MC for yield occurred when MC was applied at the early bloom and full bloom stages. Cultivars differed in yield responses to MC applied at the full bloom and post‐topping stages. Plant density influenced yield response to early MC application at the seedling stage. These results supported our hypothesis, which is helpful in guiding the rational combination of multiple MC applications according to varying conditions in view of yield formation.